Silane functionalization of WS2 nanotubes for interaction with poly(lactic acid). Issue 16 (11th April 2023) - Magee, Eimear; Tang, Fengzai; Walker, Marc; Zak, Alla; Tenne, Reshef; McNally, Tony
Abstract : Functionalisation of nanofillers is required for the promotion of strong interfacial interactions with polymers and is essential as a route for the preparation of (nano)composites with superior mechanical properties. Abstract : Functionalisation of nanofillers is required for the promotion of strong interfacial interactions with polymers and is essential as a route for the preparation of (nano)composites with superior mechanical properties. Tungsten disulphide nanotubes (WS2 NTs) were functionalized using (3-aminopropyl) triethoxysilane (APTES) for preparation of composites with poly(lactic acid) (PLA). The WS2 NTs : APTES ratios used were 1 : 1, 1 : 2 and 1 : 4 WS2 NTs : APTES. The APTES formed siloxane networks bound to the NTs via surface oxygen and carbon moieties adsorbed on the WS2 NTs surface, detected by X-ray photoelectron spectroscopy (XPS) studies and chemical mapping using energy dispersive X-ray spectroscopy in the scanning transmission electron microscope (STEM-EDS). The successful silane modification of the WS2 NTs was clearly evident with both significant peak shifting by as much as 60 cm −1 for Si–O–Si vibrations (FTIR) and peak broadening of the A1g band in the Raman spectra of the WS2 NTs. The evolution of new bands was also observed and are associated with Si–CH2 –CH2 and, symmetric and assymetric –NH 3+ deformation modes (FTIR). Further evidence for functionalization was obtained from zeta potential measurements as there was a change in surface charge from negative for pure WS2 NTs to positive for APTES modified WS2 NTs. Additionally, the thermal stability of APTES was shifted to much higher temperatures as it was bound to the WS2 NTs. The APTES modified WS2 NTs were organophilic and readily dispersed in PLA, while presence of the pendant amine and hydroxyl groups resulted in strong interfacial interactions with the polymer matrix. The inclusion of as little as 0.5 wt% WS2 NTs modified with 2.0 wt% APTES resulted in an increase of 600% in both the elongation at break (a measure of ductility) and the tensile toughness relative to neat PLA, without impacting the stiffness or strength of the polymer.